(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
Synonymy is one of the most important phenomena in lexical semantics and plays a significant role in the enrichment and expressive potential of language. The present article investigates the problem of synonymy in English and Uzbek from a comparative linguistic perspective. The study focuses on the semantic relations between lexical units that share similar meanings but differ in stylistic, contextual, or emotional nuances. Particular attention is paid to the classification of synonyms, the role of synonymy in speech expressiveness, and the structural characteristics of synonymic series in both languages. The research demonstrates that although English and Uzbek belong to different language families, they share several common principles in the formation and functioning of synonymic relations. At the same time, each language reflects its own cultural and historical development through specific lexical and stylistic features.